PROSODY FACILITATES MEMORY RECALL IN L1 BUT NOT IN L2 IN HIGHLY PROFICIENT LISTENERS. Issue 1 (March 2020) - Schmidt, Elaine; Pérez, Ana; Cilibrasi, Luca; Tsimpli, Ianthi
Abstract: Prosody is crucial for language comprehension because it highlights underlying structures. This study explores whether prosody facilitates memory recall to the same extent in L1 and L2, and whether memory recall is poorer in L2 or whether language-specific differences can mitigate L2 processing difficulties. Nineteen Greek learners of English, and a monolingual English baseline, repeated three-digit chunks with and without prosodic cues in L1 and L2. Prosody was a major facilitator of memory recall only in L1 despite the high proficiency of learners. This indicates that L2 mastery of prosody perception is hard to attain, mirroring production studies. However, when prosodic boundary cues were absent, memory recall in L2 was comparable to L1. This demonstrates that language-specific differences can attenuate more general processing difficulties in L2. This study is the first to demonstrate differences in prosodic processing in L1 and L2 resulting in poorer memory recall in L2.